Assessing The Effectiveness Of The Gorontalo Mayor's Regulations On The Implementation Of Discipline And Law Enforcement Of Health Protocols (Estudiante Law Journal, 2019)
The purpose of this research is to Know and analyze the implementation of Gorontalo Mayor's regulations on the Implementation of Discipline and Law Enforcement of Health Protocols as an Effort to Prevent and Control Corona Virus Disease 2019 in Gorontalo City and Know and analyze theconstraints of the implementation of Gorontalo Mayor's regulations on the Implementation of Discipline and Law Enforcement of Health Protocols as An Effort to Prevent and Control Corona  Virus Disease 2019 in Gorontalo City.The type of research used by researchers in compiling this research is a type of normative-empirical research using 2 (two) approaches, namely the Regulatory Approach and the case approach.  The results of this study show that:that the effectiveness of the implementation of Gorontalo mayoral regulations on the implementation of discipline and law enforcement of health protocols as an effort to prevent and control coronavirus disease2019 is still not able to effectively prevent the transmission and spread of covid-19 in the city of Gorontalo. Keywords: Effectiveness; corona virus disease 2019; Health Protocols.